Natural enemy activity following the introduction of Epidinocarsis lopezi (Hymenoptera: encyrtidae) against the cassava mealybug, Phenacoccus manihoti (Homoptera: psudococcidae), in southwestern Nigeria - Neuenschwander, Peter; Hammond, W.N.O. (Oxford University Press, 1988)
The effectiveness of the exotic South American hymenopterous parasitoid Epidinocarsis lopezi (De Santis) in controlling the cassava mealybug (CM), Phenacoccus manihoti Matile-Ferrero, in southwestern Nigeria, was assessed using emergence samples. Ten infested cassava tips were collected from each of 679 fields during four surveys over an area of 200,000 km2 in the 2 yr following establishment of the parasitoid. These samples were used to determine frequency and abundance of this and other insects associated with the CM. Survey results suggest that CM infestation levels as measured by frequency of plants showing CM damage symptoms declined as a result of the parasitoid's activity from 88% at the end of the first dry season (March 1983) to 23% in the same period the following year. E. lopezi numbers per field also declined during the same period, but parasitoid densities per infested cassava tip in both years remained the same. A sharp fall in numbers of indigenous polyphagous coccinellids on cassava, particularly of Hyperaspis spp. and to a lesser extent of Exochomus sp., was also associated with decline in CM infestation levels. By contrast, the infested tip densities of the cecidomyiid Dicrodiplosis manihoti Harris, which is specific on CM, were not affected. Other indigenous primary parasitoids of the genus Anagyrus were rare. Ten species of native hyperparasitoids were common from E. lopezi; most common were Prochiloneurus spp. and Chartocerus spp. As E. lopezi densities declined, percent hyperparasitism dropped significantly from 43.8% in March 1983 to 30.7% in March 1984, and from 35.7% in December 1983 to 17.5% in December 1984. In the last two surveys, CM densities, as determined from dissected cassava tips, were low throughout southwestern Nigeria. It is concluded that E. lopezi is responsible for declines in CM densities and damage symptoms, for reduction of coccinellid abundance via competition for a common food source, and that hyperparasitism does not prevent E. lopezi from being an efficient parasitoid.